Infant Attachment and Social Modification of Stress Neurobiology - Packard, Katherine; Opendak, Maya; Soper, Caroline Davis; Sardar, Haniyyah; Sullivan, Regina M. (Frontiers in Systems Neuroscience, 2021)
Decades of research have informed our understanding of how stress impacts the brain to perturb behavior. However, stress during development has received specific attention as this occurs during a sensitive period for scaffolding lifelong socio-emotional behavior. In this review, we focus the developmental neurobiology of stress-related pathology during infancy and focus on one of the many important variables that can switch outcomes from adaptive to maladaptive outcome: caregiver presence during infants’ exposure to chronic stress. While this review relies heavily on rodent neuroscience research, we frequently connect this work with the human behavioral and brain literature to facilitate translation. Bowlby’s Attachment Theory is used as a guiding framework in order to understand how early care quality impacts caregiver regulation of the infant to produce lasting outcomes on mental health.